ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF MANGIFERA INDICA ETHANOL AND AQUEOUS LEAVES EXTRACT AGAINST PSEUDOMONAS AERUGINOSA AND STAPHYLOCOCCUS AUREUS - Garga, M. A.; Garasin, U. M.; Abdullahi, M.; Muhammed, B. A.; Yakubu, A.; Idris, M.; Agyo-Likita, R.; Mamuda, M. A.; Ibrahim, D.; Hamza, L. M. (International Journal of Research -GRANTHAALAYAH, 2021)
The aim of this research is to investigate the antibacterial activity and identify the phytochemical constituents of Mangifera indica leafs on Pseudomonas aeruginosa and Staphylococcus aureus using disc diffusion method. The sample was collected fresh from the premises of Bioresources Development Center (BIODEC), Katsina, Katsina State and was dried and pounded into powder. The powdered leaves were extracted using ethanol and aqueous solvents. Various concentrations ranging from 500mg to 62.5mg were prepared. Test isolates were obtained from the Microbiology laboratory, Umaru Musa Yar’adua University Katsina (UMYUK) and were further authenticated using Gram staining and biochemical test. The bacterial inoculums were standardized to McFarland scale 0.5. Zones of inhibition were read after 24 hours at 370C. The results of the antibacterial study revealed that the ethanolic leaves extracts at 500mg/ml had effect on P. aeruginosa and S. aureus with zones of inhibition of 12mm and 6mm respectively. The results of the phytochemical screening revealed the presence of flavonoids, tannins, saponins, alkaloids and phenols where only alkaloids was found to be absent in the aqueous extract. There is no significant difference between the solvents and various concentrations used base on t-test data analysis.